Intravenous administration of expanded allogeneic adipose-derived mesenchymal stem cells in refractory rheumatoid arthritis (Cx611): results of a multicentre, dose escalation, randomised, single-blind, placebo-controlled phase Ib/IIa clinical trial. Issue 1 (7th June 2016) - Álvaro-Gracia, Jose M; Jover, Juan A; García-Vicuña, Rosario; Carreño, Luis; Alonso, Alberto; Marsal, Sara; Blanco, Francisco; Martínez-Taboada, Victor M; Taylor, Peter; Martín-Martín, Cristina; DelaRosa, Olga; Tagarro, Ignacio; et al.
Abstract : Objectives: To evaluate the safety and tolerability of the intravenous administration of Cx611, a preparation of allogeneic expanded adipose-derived stem cells (eASCs), in patients with refractory rheumatoid arthritis (RA), as well as to obtain preliminary clinical efficacy data in this population. Methods: It is a multicentre, dose escalation, randomised, single-blind (double-blind for efficacy), placebo-controlled, phase Ib/IIa clinical trial. Patients with active refractory RA (failure to at least two biologicals) were randomised to receive three intravenous infusions of Cx611: 1 million/kg (cohort A), 2 million/kg (cohort B), 4 million/kg (cohort C) or placebo, on days 1, 8 and 15, and they were followed for therapy assessment for 24 weeks. Results: Fifty-three patients were treated (20 in cohort A, 20 in cohort B, 6 in cohort C and 7 in placebo group). A total of 141 adverse events (AEs) were reported. Seventeen patients from the group A (85%), 15 from the group B (75%), 6 from the group C (100%) and 4 from the placebo group (57%) experienced at least one AE. Eight AEs from 6 patients were grade 3 in intensity (severe), 5 in cohort A (lacunar infarction, diarrhoea, tendon rupture, rheumatoid nodule and arthritis), 2 in cohort B (sciatica and RA) and 1 in the placebo group (asthenia). Only one of the grade 3 AEs was serious (the lacunar infarction). American College of Rheumatology 20 responses for cohorts A, B, C and placebo were 45%, 20%, 33% and 29%, respectively, at month 1, and 25%, 15%, 17% and 0%, respectively, at month 3. Conclusions: The intravenous infusion of Cx611 was in general well tolerated, without evidence of dose-related toxicity at the dose range and time period studied. In addition, a trend for clinical efficacy was observed. These data, in our opinion, justify further investigation of this innovative therapy in patients with RA. Trial registration numbers: EudraCT: 2010-021602-37; NCT01663116 ; Results.